Let
[tex] A(-6,7)\\B(-1,2) [/tex]
we know that
The points A and B must satisfy both equations
we proceed to verify each case
case A)
equation [tex] 1 [/tex]
[tex] y=x^{2} -6x-7 [/tex]
check point A
for [tex] x=-6 [/tex]
y must be [tex] 7 [/tex]
substitute
[tex] y=(-6)^{2} -6*(-6)-7 [/tex]
[tex] y=36+36-7\\ y=65 [/tex]
[tex] 65 [/tex] is not equal to [tex] 7 [/tex]
so
The system of equations is not represented by the graph
It is not necessary to check point B
case B)
equation [tex] 1 [/tex]
[tex] y=x^{2} -6x+7 [/tex]
check point A
for [tex] x=-6 [/tex]
y must be [tex] 7 [/tex]
substitute
[tex] y=(-6)^{2} -6*(-6)+7 [/tex]
[tex] y=36+36+7\\ y=79 [/tex]
[tex] 79 [/tex] is not equal to [tex] 7 [/tex]
so
The system of equations is not represented by the graph
It is not necessary to check point B
case C)
equation [tex] 1 [/tex]
[tex] y=x^{2} +6x-7 [/tex]
check point A
for [tex] x=-6 [/tex]
y must be [tex] 7 [/tex]
substitute
[tex] y=(-6)^{2} +6*(-6)-7 [/tex]
[tex] y=36-36-7\\ y=-7 [/tex]
[tex] -7 [/tex] is not equal to [tex] 7 [/tex]
so
The system of equations is not represented by the graph
It is not necessary to check point B
case D)
equation [tex] 1 [/tex]
[tex] y=x^{2} +6x+7 [/tex]
check point A
for [tex] x=-6 [/tex]
y must be [tex] 7 [/tex]
substitute
[tex] y=(-6)^{2} +6*(-6)+7 [/tex]
[tex] y=36-36+7\\ y=7 [/tex]
[tex] 7 [/tex] is equal to [tex] 7 [/tex]------->is ok
check point B
for [tex] x=-1 [/tex]
y must be [tex] 2 [/tex]
substitute
[tex] y=(-1)^{2} +6*(-1)+7 [/tex]
[tex] y=1-6+7\\ y=2 [/tex]
[tex] 2 [/tex] is equal to [tex] 2 [/tex]----->is ok
equation [tex] 2 [/tex]
[tex] x+y=1 [/tex]
check point A
for [tex] x=-6 [/tex]
y must be [tex] 7 [/tex]
substitute
[tex] -6+y=1\\ y=6+1\\ y=7 [/tex]
[tex] 7 [/tex] is equal to [tex] 7 [/tex]------->is ok
check point B
for [tex] x=-1 [/tex]
y must be [tex] 2 [/tex]
substitute
[tex] -1+y=1\\ y=1+1\\ y=2 [/tex]
[tex] 2 [/tex] is equal to [tex] 2 [/tex]----->is ok
therefore
the answer is the option D
[tex] y=x^{2} +6x+7 [/tex]
[tex] x+y=1 [/tex]